Soil erodibility results of revegetation using Bitti plant at various ages reclamation of quarry a limestone mine at PT. Semen Tonasa, Pangkep District, South Sulawesi - Nasir, Muhammad Nurhalik; Arbiwati, Dyah; Nurcholis, M.; Andarini S., Raras Nidya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Limestone mine reclamation by Limited Liability Company (LLC)/Perseroan Terbatas (PT) Semen Tonasa is carried out periodically to restore land conditions sustainably. The reclamation was carried out through revegetation using endemic plants, namely the bitter plant (Vitex colossus R.), which grows significantly in the southern part of Sulawesi. This study aims to determine the erodibility of the soil in limestone mine reclamation land planted with bitti plants. Methods: The method used is the survey method by determining the location of soil samples using the purposive sampling method based on the reclamation age planted with bitti plants in 2019, 2015 and 2010 and determining the erodibility value using the formula according to Wischmerier and Smith (1978). The parameters used included soil texture, structure, organic matter, permeability, pH, and unit weight. Findings: The results of this study indicate that the erodibility of the soil in the limestone mine reclamation land planted with bitti plants is classified as high due to the high dust content, which is influenced by the parent material. The results of this study indicate that the erodibility value of the land reclamation in 2019 was classified as moderately low to moderately high, the land reclamation in 2015 was classified as moderate to moderately high, and the land reclamation in 2010 was classified as moderate to high. Conclusion: The factor affecting the erodibility of the soil in the reclamation area is the M value (percentage of very fine silt and sand). Novelty/Originality of this Study: This study's novelty lies in examining soil erodibility changes over different reclamation ages in a limestone mine using endemic bitti plants. This research highlights the unique relationship between reclamation age and soil properties, contributing valuable insights into effective land reclamation practices in tropical karst environments.